2018
DOI: 10.1002/jat.3645
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in bile acids II. Bile acid metabolism

Abstract: One of the mechanisms of drug-induced liver injury (DILI) involves alterations in bile acid (BA) homeostasis and elimination, which encompass several metabolic pathways including hydroxylation, amidation, sulfation, glucuronidation and glutathione conjugation. Species differences in BA metabolism may play a major role in the failure of currently used in vitro and in vivo models to predict reliably the DILI during the early stages of drug discovery and development. We developed an in vitro cofactor-fortified li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 105 publications
1
41
0
4
Order By: Relevance
“…S3A). These results conform with previous studies indicating the prevalence of unconjugated BAs in rhesus macaque plasma; however, they disagree with previous studies regarding individual BAs, finding a higher percentage of unconjugated CDCA instead of DCA (46,47,72). Circulating TBA concentration in NHP plasma proved comparable to that in human plasma as reported in scientific literature, i.e.…”
Section: Nhp Ba Quantificationsupporting
confidence: 72%
See 2 more Smart Citations
“…S3A). These results conform with previous studies indicating the prevalence of unconjugated BAs in rhesus macaque plasma; however, they disagree with previous studies regarding individual BAs, finding a higher percentage of unconjugated CDCA instead of DCA (46,47,72). Circulating TBA concentration in NHP plasma proved comparable to that in human plasma as reported in scientific literature, i.e.…”
Section: Nhp Ba Quantificationsupporting
confidence: 72%
“…Additionally, though this study did not evaluate sulfated BAs, at least one previous study has reported marked differences between the extent of this BA elimination pathway in NHP versus humans (46,47). Overall, however, this laboratory animal represents a highly relevant model for the study of BA synthesis, metabolism, and pharmacology with relatively minor disparities in comparison to other models.…”
Section: Nhp Ba Quantificationmentioning
confidence: 96%
See 1 more Smart Citation
“…The relative activity of recombinantly expressed UGT1A1 and UGT2B7 isoforms was less than 1.5% of UGT1A3 activity in chenodeoxycholic acid glucuronidation (in-house data), indicating a good selectivity of chenodeoxycholic acid for UGT1A3. However, chenodeoxycholic acid would not be a useful UGT1A3 probe substrate in a more complex system such as hepatocytes, due to very high taurine and glycine conjugation rates (Thakare et al, 2018). Raloxifene, considered as a partial substrate of UGT1A8 and UGT1A10 (Kemp et al, 2002), was not included in our report, as neither UGT isoform was detected in HLMs (Fallon et al, 2013;Margaillan et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…The BAs in humans, minipigs, and hamsters conjugate mainly with glycine, while taurine amidation is predominant in mice, rat and dogs. It has been also discovered that less sulfation occurs in rat and mice compared to human and chimpanzee (Thakare et al, 2018b;Thakare et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%